ANALISIS PENGARUH KREDIT CEPAT AMAN (KCA), KREDIT ANGSURAN SISTEM FIDUSIA (KREASI), KREDIT ANGSURAN SISTEM GADAI (KRASIDA), DAN KREDIT SERBA GUNA (KRESNA) TERHADAP PENDAPATAN SEWA MODAL PADA PT. PEGADAIAN (PERSERO) KANWIL VI MANADO - Siwu, Jane Eiva; Karamoy, Herman; Pangemanan, Sifrid (Universitas Sam Ratulangi, 2013)
The services product of PT. Pegadaian ( Persero) , are Credit Fast Secure, Installment Loans Fiduciary System, Installment Loans Pawn System, and Multipurpose Loan. Customer will repay the loan with interest in this case is a capital lease is revenue that received of PT. Pegadaian ( Persero) by loans extended. In line with the growth of the existing business can be seen the increase of lease income on lending capital that during 2006 to 2011. This research is analyze the causal’s relationship to examine the effect of the fact and phenomena and seek factual information to research that explained on the effect of Credit Fast Secure, Installment Loans Fiduciary System, Installment Loans Pawn System, Multipurpose Loan on Capital Lease Revenue at PT. Pegadaian ( Persero) Regional Office VI Manado which is a services products on offer to the public. From these research it can be concluded that Credit Fast Secure, Installment Loans Fiduciary System, Installment Loans Pawn System, Multipurpose Loan, have influence on Capital Lease Revenue at PT. Pegadaian ( Persero) Regional Office VI Manado have increase from year to year.